Articaine and lidocaine for maxillary infiltration anesthesia. - Vähätalo, K. (American Dental Society of Anesthesiology, 1993)
This study was undertaken to compare the anesthetic properties of articaine hydrochloride with 1:200,000 epinephrine (Ultracain DS) and lidocaine with 1:80,000 epinephrine (Xylocain-Adrenalin) for maxillary infiltration anesthesia. Twenty healthy dental student volunteers were included in this double-blind study. Each subject received 0.6 mL of each test solution at different times. Infiltration anesthesia was performed on the upper lateral incisor. The onset and duration of anesthesia were monitored using an electric pulp tester. No statistically significant differences were seen in the onset and duration of anesthesia between the articaine and lidocaine solutions.